A Statistical Method for Reassociating Human Tali and Calcanei from a Commingled Context1. Issue 2 (1st June 2017) - Anastopoulou, Ioanna; Karakostis, Fotios A.; Borrini, Matteo; Moraitis, Konstantinos
Abstract: In a commingled context, assessing that a talus and a calcaneus correspond to the same individual could become a primary step for accurately sorting human remains. For this purpose, the lengths and widths of the trochlea, posterior calcaneal articular surface, and posterior talar articular surface were measured in 197 individuals (105 males, 92 females) from the Athens Collection. A total of 12 highly accurate equations for reassociating tali and calcanei were developed, using simple and multiple linear regression analysis and they were found to be suitable for sorting commingled human remains. Bilateral asymmetry and sex did not have an effect on the accuracy of the method.